2011
DOI: 10.1159/000324535
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Thermostable Lipase Production by a Genotypically Identified Extremophilic <i>Bacillus subtilis</i> NS 8 in a Continuous Bioreactor

Abstract: Bacillus strain NS 8, a lipase-producing bacterium isolated from a Malaysian hot spring, is able to tolerate a broad range of temperature and pH, which makes it beneficial for this study. It generated PCR products with molecular weight of 1,532 bp, and the 16S rRNA sequence analysis identified it as Bacillus subtilis with accession number AB110598. It showed a 71% similarity index with B. subtilis using Biolog Microstation System. Its lipase production was optimized using a shake flask system by changing the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…This study showed that combinations of probiotics, oligosaccharides, and/or berberine could significantly increase fecal lipase, protease, and amylase activity to some extent. The reason may be that the probiotics can produce these enzymes or stimulate endogenic excretion (21). It was reported that diets supplemented with probiotics could significantly improve carbohydrate digestibility in the small intestine (22).…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that combinations of probiotics, oligosaccharides, and/or berberine could significantly increase fecal lipase, protease, and amylase activity to some extent. The reason may be that the probiotics can produce these enzymes or stimulate endogenic excretion (21). It was reported that diets supplemented with probiotics could significantly improve carbohydrate digestibility in the small intestine (22).…”
Section: Discussionmentioning
confidence: 99%
“…An increased agitation speed beyond the optimum could create shear forces that negatively impact the cell biomass integrity, which therefore affects the enzyme productivity [54]. Likewise, other studies have shown that lipase production by Bacillus licheniformis [55] and B. subtilis [56] was optimum at 140 rpm and 150 rpm, respectively. The size of the starter culture influences enzyme production by bacterial strains; overpopulation of the culture medium at the inception of fermentation could be a limiting factor in terms of the optimal enzyme yield, as this might result in the quick depletion of nutrients and dissolved oxygen [47].…”
Section: Discussionmentioning
confidence: 99%